3-year invasive disease-free survival with chemotherapy de-escalation using an 18F-FDG-PET-based, pathological complete response-adapted strategy in HER2-positive early breast cancer (PHERGain): a randomised, open-label, phase 2 trial - Perez-Garcia, Jose Manuel; Cortés, Javier; Ruiz-Borrego, Manuel; Colleoni, Marco; Stradella, Agostina; Bermejo, Begoña; Dalenc, Florence; Escrivá-de-Romaní, Santiago; Calvo Martínez, Lourdes; Ribelles, Nuria; Marmé, Frederik; Cortés, Alfonso; et al. (The lancet, 2024)
Background - PHERGain was designed to assess the feasibility, safety, and efficacy of a chemotherapy-free treatment based on a dual human epidermal growth factor receptor 2 (HER2) blockade with trastuzumab and pertuzumab in patients with HER2-positive early breast cancer (EBC). It used an 18fluorine-fluorodeoxyglucose-PET-based, pathological complete response (pCR)-adapted strategy. - Methods - PHERGain was a randomised, open-label, phase 2 trial that took place in 45 hospitals in seven European countries. It randomly allocated patients in a 1:4 ratio with centrally confirmed, HER2-positive, stage I-IIIA invasive, operable breast cancer with at least one PET-evaluable lesion to either group A, where patients received docetaxel (75 mg/m2, intravenous), carboplatin (area under the curve 6 mg/mL per min, intravenous), trastuzumab (600 mg fixed dose, subcutaneous), and pertuzumab (840 mg loading dose followed by 420 mg maintenance doses, intravenous; TCHP), or group B, where patients received trastuzumab and pertuzumab with or without endocrine therapy, every 3 weeks. Random allocation was stratified by hormone receptor status. Centrally reviewed PET was conducted at baseline and after two treatment cycles. Patients in group B were treated according to on-treatment PET results. Patients in group B who were PET-responders continued with trastuzumab and pertuzumab with or without endocrine therapy for six cycles, while PET-non-responders were switched to receive six cycles of TCHP. After surgery, patients in group B who were PET-responders who did not achieve a pCR received six cycles of TCHP, and all patients completed up to 18 cycles of trastuzumab and pertuzumab. The primary endpoints were pCR in patients who were group B PET-responders after two treatment cycles (the results for which have been reported previously) and 3-year invasive disease-free survival (iDFS) in patients in group B. The study is registered with ClinicalTrials.gov (NCT03161353) and is ongoing. - Findings - Between June 26, 2017, and April 24, 2019, a total of 356 patients were randomly allocated (71 patients in group A and 285 patients in group B), and 63 (89%) and 267 (94%) patients proceeded to surgery in groups A and B, respectively. At this second analysis (data cutoff: Nov 4, 2022), the median duration of follow-up was 43·3 months (range 0·0-63·0). In group B, the 3-year iDFS rate was 94·8% (95% CI 91·4-97·1; p=0·001), meeting the primary endpoint. No new safety signals were identified. Treatment-related adverse events and serious adverse events (SAEs) were numerically higher in patients allocated to group A than to group B (grade ≥3 62% vs 33%; SAEs 28% vs 14%). Group B PET-responders with pCR presented the lowest incidence of treatment-related grade 3 or higher adverse events (1%) without any SAEs. - Interpretation - Among HER2-positive EBC patients, a PET-based, pCR-adapted strategy was associated with an excellent 3-year iDFS. This strategy identified about a third of patients who had HER2-positive EBC who could safely omit chemotherapy. - Funding - F Hoffmann-La Roche.